Epigenetics and Female Reproductive Aging - Chamani, Isaac J.; Keefe, David L. (Frontiers in Endocrinology, 2019)
With more women than ever waiting until a more advanced age to have children, there exists a newfound urgency to identify the various implications aging has on human reproduction, and understand the disrupted biological processes that result in these changes. In this review, we focus on one recent area of study: the age related epigenetic changes that have been found in female reproductive organs, and the effect these changes may contribute to reproductive outcomes.